2014
DOI: 10.1111/1365-2656.12185
|View full text |Cite
|
Sign up to set email alerts
|

The invasion of southern South America by imported bumblebees and associated parasites

Abstract: Summary The Palaearctic Bombus ruderatus (in 1982/1983) and Bombus terrestris (1998) have both been introduced into South America (Chile) for pollination purposes. We here report on the results of sampling campaigns in 2004, and 2010-2012 showing that both species have established and massively expanded their range. 2. Bombus terrestris, in particular, has spread by some 200 km year À1 and had reached the Atlantic coast in Argentina by the end of 2011. Both species, and especially B. terrestris, are infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
3
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(173 citation statements)
references
References 68 publications
4
159
3
7
Order By: Relevance
“…Parasite spillover consequences for wild pollinators could be huge and remain largely underestimated (F€ urst et al, 2014), because infections can strongly reduce fitness, survival and even foraging behaviour in wild populations (Graystock et al, 2013b, Garibaldi et al, 2016Meeus et al, 2011). In Patagonia, the spectacular regression of the endemic B. dahlbomii following B. terrestris invasion has been suspected to be caused by pathogen spillover (Morales et al, 2013;Schmid-Hempel et al, 2014). In the United States, Cameron et al (2011) observed a correlation between N. bombi infections and declining populations of eight native bumblebee species.…”
Section: Apparent Competition: Spillover Of Shared Parasites and Pathmentioning
confidence: 99%
“…Parasite spillover consequences for wild pollinators could be huge and remain largely underestimated (F€ urst et al, 2014), because infections can strongly reduce fitness, survival and even foraging behaviour in wild populations (Graystock et al, 2013b, Garibaldi et al, 2016Meeus et al, 2011). In Patagonia, the spectacular regression of the endemic B. dahlbomii following B. terrestris invasion has been suspected to be caused by pathogen spillover (Morales et al, 2013;Schmid-Hempel et al, 2014). In the United States, Cameron et al (2011) observed a correlation between N. bombi infections and declining populations of eight native bumblebee species.…”
Section: Apparent Competition: Spillover Of Shared Parasites and Pathmentioning
confidence: 99%
“…Crithidia bombi infects bees in many ecosystems worldwide (Cameron et al., 2011; Schmid‐Hempel, Schmid‐Hempel, Brunner, Seeman, & Allen, 2007), where phytochemical exposure will be complex and varied. The parasite's deleterious effects on infected bees (Brown, Schmid‐Hempel, & Schmid‐Hempel, 2003; Sadd & Barribeau, 2013), including threatened native species (Schmid‐Hempel et al., 2014), indicate its ecological and practical importance (Sadd & Barribeau, 2013). …”
Section: Study Systemmentioning
confidence: 99%
“…2014; Schmid‐Hempel et al . 2014). EIDs are known to be a major threat to the most widely used commercial pollinator, the honeybee ( Apis mellifera ), with the exotic ectoparasitic mite, Varroa destructor , meriting particular attention.…”
Section: Introductionmentioning
confidence: 99%